An Old English Primer - ANDREI, Crișan; BUZEC, Mihaela; PAPAHAGI, Adrian (2022)
Cumpărați cartea în format tipărit.This little book is designed to accompany students during their courses and seminars of Old English language and literature. The first part of the primer is an introduction to the language. It discusses spelling, pronunciation, word formation, morphology, and syntax.Essential morphological paradigms and phonological phenomena can be found in a nutshell.